The Development and Health Advocate Drive: Boromarajonani College of Nursing, Chiang mai - วันไชยธนวงค์ วราพร; อุ่นบ้าน พิมพ์ใจ; มนัสพรหม พจนีย์ (Journal of Nurses Association of Thailand Northern Office, 2017)
The aim of this research is to explore health advocate drive in Boromarajonani College of Nursing. The samples were 3 groups follow by the step of research. Step 1 was to study the process of health statute drive of Boromarajonani College of Nursing, Trang, The samples were 1 director, 5 instructors, 5 personnel and 5 nursing students. Step 2 was developed and drove the health statute of Boromarajonani College of Nursing, Chiangmai. The samples were the 685 personnel of Boromarajonani College of Nursing, Chiangmai in academic year 2015 consist of 59 administrators, 45 personnel and 581 nursing students. Step 3 was to study the result of this drove. The samples were the 270 personnel of Boromarajonani College of Nursing, Chiangmai in academic year 2015 consist of 23 administrators, 17 personnel and 230 nursing students. The research tool was the questionnaire of using the health statute, there were 3 parts. 1) General data. 2) Practical of heath statute. 3) limitation, barrier and recommendation. The research tool was evaluated by 3 experts, the Index of Consistency/IOC was 0.67. The date analysis for result of the health statute drive was Means and Standard Deviation. The data analysis for the advantage, disadvantage, limitation and barrier of the health statute drive were content analysis. The study reveals The process of health advocate drive of Boromarajonani College of Nursing, Trang, policy announcement – drive policy declaration the under meeting of nursing student, clubs, instructors and personals. All activities applied to the family – like club and set to the success indicator. The drive process was motivation, invitation, praise, respect and generosity. The process of health advocate drive of Boromarajonani College of Nursing, Chiangmai, start at 1) setting the leader 2) leader’s training 3) evaluate situation 4) grouped the needs 5) health advocate draft 6) public hearing 7) health advocate declaration 8) follow up and evaluation. The health advocate included 10 items. They were 1) exercise every Thursday 2) hygienic food and drink 3) clean and coded uniform 4) annual physical checkup 5) listen to music at lunch break 6) 5 minutes meditation before attend class and for 20 minutes at lunch break 7) entered Buddha room and eat the vegetarian food every Monday 8) monthly - offer the monk food and attend the Buddha speech every the 3rd Thursday 9) Monthly cleaning the collage and yearly afforest 10) grouping the garbage. The result of the health advocate drive of Boromarajonani College of Nursing, Chiangmai, reveals that the overall of practice was good level, Means as 2.89. Health outcome were long term physical health, long term mental health, good relationship, good shape and feature, consciousness.